X-ray Reflectivity Studies on the Mixed Langmuir-Blodgett Monolayers of Thiol-Capped Gold Nanoparticles, Dipalmitoylphosphatidylcholine, and Sodium Dodecyl Sulfate - Chen, Yi-Tang (Langmuir : the ACS journal of surfaces and colloids, 2017)
Langmuir-Blodgett monolayers of thiolated gold nanoparticles mixed with dipalmitoylphosphatidylcholine/sodium dodecyl sulfate (DPPC/SDS) were investigated by combining the X-ray reflectivity, grazing-incident scattering, and TEM analyses to reveal the in-depth and in-plane organization and the 2D morphology of such mixed monolayers. It was found that the addition of a charged single-tail surfactant to the thiolated Au nanoparticle monolayer helps to stabilize the Au nanoparticle monolayer and to strengthen the mechanical property of the mixed monolayer film. For mixing with lipids, it was found that the thiolated gold nanoparticles could be pushed on top of the lipid monolayer when the mixed monolayer is compressed. At a typical comparable total surface area ratio of gold nanoparticle to lipid, the thiolated gold nanoparticles could form a uniform domain on top of the DPPC monolayer. When there are more thiolated gold nanoparticles than that could be supported by the lipid monolayer, domain overlapping could occur to form bilayer gold nanoparticle domains at some regions. At low total surface area ratio of thiolated gold nanoparticle to lipid, the thiolated gold nanoparticles tend to form a connected threadlike aggregation structure. Evidently, the morphology of the thiolated gold nanoparticle monolayer is highly depending on the total surface area ratio of the thiolated gold nanoparticle to lipid. SDS is found to have a dispersion power capable of dispersing the originally uniform Au-8C nanoparticle domain of the mixed Au-8C/DPPC monolayer into a foamlike structure for the mixed Au-8C/SDS/DPPC monolayer. It is evident that not only the concentration ratio but also the size and shape of the template formed by the amphiphilic molecules and their interaction with the thiolated gold nanoparticles can all have great effects on the organizational structure as well as morphology of the thiolated gold nanoparticle monolayer